Roles of N and P in Soil Acidification, Metals Mobilization and Bioavailable Concentration-Based Soil Fertility Assessment in Tea Plantations in Yunnan, China - Fuxin Ye; Ziwen Luo; Yongwang Ju; Qin Huan; Xue Liu (Agriculture)
Tea yield is determined by soil fertility. An elemental bioavailable-content-based fertility assessment is more reliable than that of total content. In tea plantations, soil acidification occurs, affecting metals’ bioavailability and fertility, yet the relations are unclear. Soils (n = 190) were sampled in five major tea-producing regions in Yunnan, China. Bioavailable concentrations of fertilizers (N and P) and essential metals (Ca, Mg, Fe, Mn, Cu and Zn) were analyzed and involved in the fertility evaluation. Soils were acidified (pH = 3.44–5.53), and were partially attributed to excess N-fertilization (R = −0.26; p < 0.01). Soil acidification increased Mg, Fe and Mn bioavailability (R = −0.021, −0.087 and −0.13). P played an important role in improving metals’ bioavailability (R = 0.20–0.48; p < 0.01). Bioavailable metals showed strong heterogeneity. Therefore, the nutritional level distributions of individual indices were complex and inconsistent, so multi-indices were used to achieve more accurate assessments. This study clarified the strong correlation between N-fertilization and soil acidification, and the key role of P in improving metals’ bioavailability and fertility. The data suggest that bioavailable Cu and Zn are suitable for plant growth, Ca and Mg should be enhanced without decreasing P bioavailability, and the potential toxic effect of excessive Mn should be paid attention. The information helps to strategize scientific fertilization and management.